1. -7x - 2y = -13
2. x - 2y = 11
3. x = 2y + 11
4. Substitute the expression for x from step 3 into equation 1 to solve for y: -7(2y + 11) - 2y = -13
5. Simplify the equation from step 4: -14y - 77 - 2y = -13
6. Combine like terms in the equation from step 5: -16y - 77 = -13
7. Add 77 to both sides of the equation from step 6 and simplify: -16y = 64
8. Solve for y by dividing both sides of the equation from step 7 by -16: y = -4
9. Substitute the value of y from step 8 into the expression for x from step 3: x = 2(-4) + 11
10. Simplify the expression from step 9: x = 3
11. Verify the solution by substituting the values of x and y from steps 9 and 8, respectively, into equation 2: 3 - 2(-4) = 11
Put the steps in order that are used to solve the following systems of equations by substitution.
-7x-2y= -13
x-2y = 11
-16y = 64
= x-2y = 11 --> x = 2y + 11
-14y - 77 - 2y = - 13
-7(2y + 11) - 2y = - 13
(3, -4)
-16у - 77 = -13
x + 8 = 11
y = -4
x = 3
x - 2 (-4) = 11
Put the steps above in the right order, only use the numbers I listed above.
1 answer